Consumer competency and relationship between dissatisfaction and complaint behaviour among mobile telecommunication network consumers in Lagos, Nigeria - Chinedu, Anyanwu Hilary (2017)
Mobile Telecommunication Network (MTN) consumers in Nigeria have been engulfed with substandard services contrary to the promises of MTN upon entry into Nigerian telecommunication market. High prevalence level of predicaments towards MTN consumers for many years without a lasting solution emphasized the significance of the present study, “Effects of consumer competency on the relationship between dissatisfaction and complain behaviour among MTN consumers in Nigeria”. Among the numerous problems of MTN consumers are unsubscribed and unsolicited caller tunes with charges, lack of knowledgeable staff, high tariff and network fluctuations, and breach of privacy. Several studies on consumer dissatisfaction and complain behaviour have been conducted in Western and Asian countries with little focus on the African context especially Nigeria. Moreover, researchers have never incorporated the effects of consumer competency on the relationship between dissatisfaction and complain behaviour. The study adopted Hawkins et al. (2004) consumer behavioural framework, and self-efficacy theory to help the explanation of the main variables. These theories guided the formulation of the study’s framework through which the six objectives of the study were achieved. The study employed a quantitative approach with correlational and survey designs. The data was collected with a structured questionnaire at Festac town, Lagos state of Nigeria. It involved 385 respondents through stratified sampling method. The data were analysed using IBM SPSS version 22. The sample was tested and found to have been distributed normally. The study found that 43.9% of MTN consumers were highly dissatisfied; 74.8% were highly competent; and 35.1% were active complainers. A chi-square test revealed that female consumers are more active in complaining than male consumers, and older MTN consumers were more active complainers than young and middle aged consumers. In addition, MTN consumers with below tertiary education were found to be active complainers than those that attained tertiary education. High income earners were found to be more active in complaining than middle and low income earners. Also, a significant negative relationship was found between dissatisfaction and complain behaviour. Regression analysis revealed that only religion (β=.15) and level of income (β=.12) out of the six background variables made unique significant contributions to complain behaviour. Dissatisfaction (β=-.33) made significant contributions to complain behaviour after controlling the effects of demographic variables. Furthermore, competency was found to be negatively mediating the relationship between dissatisfaction and complain behaviour. The findings imply that demographic variables offer limited explanation of consumers’ behaviour in a dissatisfaction scenario. It further implied that highly dissatisfied MTN consumers adopted passive complain behaviours. Interestingly, it indicated that competent consumers tend to complain more than incompetent consumers, and thus contributed to the body of knowledge, most notably on the significant role of competency among consumers. MTN should install more equipment to improve their network quality, and establish a conducive complaining platform as a way of encouragement to dissatisfied consumers, hence complain offers them the opportunity to be aware of the causes and magnitude of dissatisfaction.